2007
DOI: 10.1128/jb.01163-07
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Pore Mutants of theVibrio choleraePorin OmpU

Abstract: General-diffusion porins form large ␤-barrel channels that control the permeability of the outer membrane of gram-negative bacteria to nutrients, some antibiotics, and external signals. Here, we have analyzed the effects of mutations in the OmpU porin of Vibrio cholerae at conserved residues that are known to affect pore properties in the Escherichia coli porins OmpF and OmpC. Various phenotypes were investigated, including sensitivity to ␤-lactam antibiotics, growth on large sugars, and sensitivity to and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…In earlier studies, it was shown that a negatively charged residue D116 of V. cholerae OmpU influenced the permeation and binding of hydrophilic compounds, including β-lactam antibiotics and Na-deoxycholate bile salt [31]. In the wild-type V. cholerae strain A1552 the aspartic acid residue is at position 114 instead of 116.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies, it was shown that a negatively charged residue D116 of V. cholerae OmpU influenced the permeation and binding of hydrophilic compounds, including β-lactam antibiotics and Na-deoxycholate bile salt [31]. In the wild-type V. cholerae strain A1552 the aspartic acid residue is at position 114 instead of 116.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular basis of C1q binding to bacterial porins has not been clarified. Earlier studies suggested that residue D116 (D114 in our strain) of OmpU protein might bind to membrane-targeting antibiotics and, thus, confer antibiotic resistance to V. cholerae [31]. We anticipated that the homologous pore-exposed residue D114 may control channel properties or ligand binding of the OmpU porins of V. cholerae.…”
Section: Discussionmentioning
confidence: 99%
“…OmpF and OmpC are the most studied classical porins in Gram-negative bacteria and are highly conserved in the entire Enterobacteriaceae family (Masi & Pagès, 2013;Pagel et al, 2007;Tsai et al, under high osmolarity conditions (i.e. nutrient rich environment) or acidic pH, OmpF expression is downregulated and OmpC is upregulated, resulting in increased resistance to beta-lactams.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mutations in loop 3 of the porin PIB of Neisseria gonorrhoeae confer resistance to penicillin and tetracycline in strains that simultaneously overexpress an efflux pump due to an mtrR mutation (189,190). In Vibrio cholerae, a D116A mutation in OmpU, which was predicted to be an antibiotic binding site, leads to increased resistance to cephalosporins (193). On the other hand, imipenem binding in P. aeruginosa OprD necessitates the presence of intact loops 2 and 3 (185), while external loops 5, 7, and 8 served to constrict the OprD channel entrance and prevent the nonspecific passage of antibiotics (96).…”
Section: Resistance Due To Mutations In Porin-encoding Genesmentioning
confidence: 99%